ANALYSIS OF THE USING OF E-MONEY IN INDUSTRIAL REVOLUSTION 4.0 - Mustikawati, Mustikawati; Fadila, Fadila; Muharir, Muharir (I-Economics, 2019)
Recently, the financial technology (fintech) issue has risen in significance impact. Thus, it cannot be denied, fintech has been involved in daily transaction. It is such as payment, bonds transaction, loan, and other. The society tends to use the non-cash transaction because it gave convenience and time efficiency. The aim of this research is to discuss how the law of the use of E-Money (Electronic money) in non-cash transaction in Indonesia. The method was conducted by library research. The findings of the research; there are the different opinions among academicians and ulamas. The first opinion is based on Hanafi Madzhab and the second opinion is based on Syafei madzhab. The Hanafi Madzhab allows the Electronic money without any doubt, but Syafei Madzhab elaborates that in muamalah transaction so there must be a clear Akad in every transaction